Analysis of Adolescent Hemoglobin Levels on Knowledge, Body Mass Index, and Menstrual Patterns - Siti Mas'odah; Ratih Dewi Dwiyanti; Ricko Dharmadi Utama (Baiman Bauntung Batuah Center, 2021)
Anemia can be related to several factors, including knowledge, body mass index, and menstrual patterns. Adolescent girls are a high-risk group who experience anemia. This study aims to analyze the hemoglobin levels of adolescent girls about knowledge, body mass index, and patterns menstrual. Information on the relationship between hemoglobin levels and these factors expects to be a reference for strategies to overcome anemia in adolescent girls. The sample of this research is the students of Martapura Indonesia vocational high school, totaling 45 people. Data collection includes weight and height measurements, hemoglobin examination (using Easy Touch GCHb), and questionnaires. Data analysis used bivariate analysis of chi-square test with 0.05 with 95% confidence degree. Results Respondents had fewer hemoglobin levels 47%, normal 53%. The body mass index value of respondents is less than 85%, normal 13%, excess 2%. The respondent's menstrual pattern obtained 26% abnormal data, 74% normal data. Knowledge of anemia of respondents with enough category 34%, good category 66%. The conclusion is that there is no relationship between hemoglobin levels and body mass index (p-value 0.281), menstrual patterns (p-value 0.073), and knowledge of anemia (p-value 0.402) in adolescent girls. Hemoglobin levels may more influence by the consumption pattern of foods containing iron, so it recommends that young women consume more iron-rich foods and avoid the simultaneous consumption of substances that inhibit their absorption, such as tea and coffee.